(untitled) (International Congress on Economics, Management and Business Studies, 2026)
In the current conditions of increasing global competition and development in the world, the role of industry in the socio-economic development of the country and in providing the population with decent living conditions is great, and its development is of great importance. Industry accounts for 26.0% of global GDP and 23.1% of total employment [1]. Specifically, this figure is 24.4% in Germany, 37.5% in Norway, 25.2% in Poland, and 28.6% in Kazakhstan [2]. Industry also plays an important role in the socio-economic development of countries, the satisfaction of people’s needs for high-tech products, and the growth of the state’s export potential.